Dictionary as Commentary - Arabic Lexicography in the Post-Formative Period - Lindermann, Colinda, (Global Arabic Literary Cultures ;, 2025)
This is the first book-length study of Arabic lexicography in the post-formative period (ca. 1200-1800). It provides a window into the dynamics of the discipline and the intellectual debates that unfolded in the study of the Arabic language. With a focus on speech errors and loanwords, the author explains how scholars integrated new language phenomena into tradition. By reading the dictionary as a form of commentary that departs from its master text to expand and challenge its content, this book offers a new understanding of the vibrant field of Arabic lexicography and commentary culture at large.